In Vitro Activity of Cefepime against Multidrug-Resistant Gram-Negative Bacilli, Viridans Group Streptococci and Streptococcus pneumoniae from a Cross-Canada Surveillance Study. (1999) - Low, Donald E; de Azavedo, Joyce; Canadian Bacterial Surveillance Network,; Davidson, Ross
Abstract : OBJECTIVE: To determine the in vitro activity of cefepime against multidrug-resistant Gram-negative bacilli and Gram-positive cocci obtained from an ongoing cross-Canada surveillance study. DESIGN: Clinical isolates of aerobic Gram-negative bacilli with inducible and constitutive chromosomally mediated cephalosporinases, viridans group streptococci and Streptococcus pneumoniae were collected from laboratories serving hospitals, nursing homes and physician offices in the community from across Canada during 1996 and 1997. Laboratories were asked to submit only clinically relevant nonduplicate isolates for susceptibility testing. In vitro antimicrobial susceptibility testing was carried out on all isolates of Gram-negative and viridans group streptococci. S pneumoniae were characterized as penicillin susceptible, intermediately resistant or highly resistant. Nonsusceptible isolates were defined as being intermediately or highly resistant (minimal inhibitory concentrations [MIC] greater than 0.06 mg/L). Only isolates of S pneumoniae that were nonsusceptible to penicillin were selected for further study. MICs were determined using a microbroth dilution technique according to the National Committee of Clinical Laboratory Standards. RESULTS: A total of 727 Gram-negative bacilli samples were collected. No resistance to cefepime was detected with Citrobacter freundii, Serratia marcescens, Morganella morganii and Enterobacter species. Of these strains, Enterobacter species and C freundii were the most resistant to ceftazidime, cefotaxime and ceftriaxone with MIC90S of 32 mg/L or greater and resistance rates of 6% or greater. Resistance rates of Pseudomonas aeruginosa and Acinetobacter species to cefepime were 4.8% and 3%, respectively. The two organisms had similar rates of resistance to ceftazidime. Less than 3% of the Gram-negative bacilli were resistant to imipenem and meropenem. There were 153 viridans group streptococci, of which 22 (14.4%) were resistant to penicillin. Of 1287 S pneumoniae samples, 193 (15%) were nonsusceptible to penicillin. Cefepime, ceftriaxone and cefotaxime had comparable activity against all isolates of viridans group streptococci and S pneumoniae . CONCLUSIONS: Cefepime demonstrated excellent in vitro activity against Gram-negative bacilli with inducible and constitutive chromosomally mediated cephalosporinases, and had equal or superior activity versus comparator beta-lactams against all isolates of viridans group streptococci and S pneumoniae .